Genetic and epigenetic variation of the glucocorticoid receptor (NR3C1) in placenta and infant neurobehavior. Issue 7 (19th June 2012) - Bromer, Cailey; Marsit, Carmen J.; Armstrong, David A.; Padbury, James F.; Lester, Barry
Abstract The intrauterine environment can impact the developing infant by altering the function of the placenta through changes to the epigenetic regulatory features of this tissue. Genetic variation, too, may impact infant development or may modify the relationship between epigenetic alterations and infant outcomes. To examine the associations of these variations with early life infant neurodevelopment, we examined the extent of DNA methylation of the glucocorticoid receptor gene (NR3C1) promoter and a common single nucleotide polymorphism in the promoter region in a series of 186 placentas from healthy newborn infants. We associated these molecular features with specific summary measures from the NICU Network Neurobehavioral Scales. After controlling for genotype and confounders, we identified significant associations of NR3C1 methylation with infant quality of movement (p = .05) and with infant attention (p = .05), and a potential interaction between methylation and genotype on infant attention score. These results suggest that epigenetic alteration of the NR3C1 gene in the placentas of genetically susceptible infants can have impacts on neurodevelopment which may have lifelong impact on neurobehavioral and mental health outcomes. Further research is needed to more precisely define these relationships and the interaction between epigenetic alterations and genetic variations on infant health. © 2012 Wiley Periodicals, Inc. Dev Psychobiol 55: 673–683, 2013.